2019
DOI: 10.1186/s13104-019-4513-8
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of hepatic and kidney dysfunction among newly diagnosed HIV patients with viral hepatitis infection in Cape Coast, Ghana

Abstract: Objective HIV positive individuals infected with viral hepatitis B (HBV) or C (HCV) are at an increased risk of progression to kidney and liver failures. Therefore, prior to initiation of antiretroviral therapy, early diagnosis and initiation of appropriate treatment protocols are imperative for co-infected individuals. This study evaluated the prevalence of HBV and HCV, and extent of liver and renal dysfunction among 90 newly diagnosed HIV patients attending the Cape Coast Teaching Hospital HIV c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…CR can be used to assess kidney function [ 39 ]. The study based on 90 newly diagnosed HIV patients with viral hepatitis infection in Cape Coast Teaching Hospital HIV clinic showed that severe kidney malfunction (chronic kidney disease stage 4, with eGFR < 15 mL/min/1.73 m 2 ) was only and nearly significant in those with HIV1/HBV [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…CR can be used to assess kidney function [ 39 ]. The study based on 90 newly diagnosed HIV patients with viral hepatitis infection in Cape Coast Teaching Hospital HIV clinic showed that severe kidney malfunction (chronic kidney disease stage 4, with eGFR < 15 mL/min/1.73 m 2 ) was only and nearly significant in those with HIV1/HBV [ 31 ].…”
Section: Discussionmentioning
confidence: 99%